The Role of Economic Sectors on Carbon Emissions in Indonesia - Widhawati, Pramitta; Lukis Panjawa, Jihad; Aji Prakoso, Jalu; Sugiharti, Rr. Retno (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2024)
Human activities’ negative impacts are thought to be causing increasing environmental damage and ongoing global climate change. This study aims to evaluate the impact of economic activity, particularly activities in the agriculture and industry sectors, on carbon dioxide emissions based on the STIRPAT model approach. Focusing on Indonesia and using time series data from the World Bank from 1990-2022, this research uses the Autoregressive Distributed Lag -Error Correction Model (ARDL-ECM)method to capture the long-term and short-term relationship. The results show that the STIRPAT model is robust in modelling the impact of economic activities on environmental degradation. The variable of interest of this research is renewable energy consumption, which plays a proxy in the technology and eases carbon emissions in the manufacturing and service sectors. So that, by increasing renewable energy consumption helps reduce carbon emissions in both the manufacturing and service sectors.